The transition of small Spanish wineries toward multi-channel distribution: The role of ambidexterity. Issue 1 (20th September 2019) - Calderón, Haydeé; Fayos, Teresa; Frasquet, Marta
Abstract : Purpose: This paper aims to analyses the development of exploitation and exploration capabilities, and the role of ambidexterity, in the evolution of small Spanish wineries toward multi-channel distribution systems. Design/methodology/approach: A qualitative methodology based on the analyses of multiple cases supported by a computer assisted qualitative data analysis software with an abductive approach was used to study the relationship between ambidexterity and the multi-channel integration of six wineries. Findings: Companies with more advanced multi-channel distribution systems have more developed ambidexterity capabilities. This ambidexterity stems fundamentally from the ability to simultaneously maintain relations with distributors and innovate and search for creative ways to satisfy new customers. Research limitations/implications: The research is based on insights from companies based in Spain. Practical implications: Spanish small and medium enterprises in the sector are in an underdeveloped phase of multi-channel integration. To be successful in this process, these companies must combine exploitation and exploration capabilities. Social implications: If the company is able to develop an integrated multi-channel distribution system leading to an omnichannel system, consumers will benefit from it, getting complete information at each specific stage of shopping. Originality/value: This study provides the first description in academic literature of the usefulness of the concept of ambidexterity as a dynamic capability to explain the degree of development and multi-channel integration.